The role of culture paradifm for creation the ХХІ Сentury life-forming model - Hrabovska Іryna (Professional Pedagogics, 2018)
In article the culture nature essence is analysed, the question of maintenance of a culture paradigm of education is considered, the important role of humanitarian aspects of forming of the personality is noted, ways of recovery from the crisis of the present by implementation of culture disciplines in educational process are outlined, the educational role of culture cycles for forming of cultural identity of younger generation is noted. In article the world outlook and educational mission of culture for formation of national self-identification through mastering cultural symbols and attributes of culture is described, conditions of forming of national self-identification of the personality are noted. It is emphasized that culture disciplines in curricula of comprehensive schools, professional and higher educational institutions it is necessary to regard as attempt of compensation of emotional depletion and internal devastation of youth at a stage of a technocratisation of educational process. The common cultural competence as one of important key competence of the Council of Europe created thus, will promote culture and universal understanding youth of a scientific picture of the world, to expansion of outlook, forming of system and practical and cross-cultural skills for creation of society of cross-cultural tolerant coexistence which metasubject role – XXI century life-forming model. On the basis of the analysis of theoretical sources the considerable potential of a culture paradigm for ensuring humanization of educational activity is realized.